2014
DOI: 10.1021/cm5024579
|View full text |Cite
|
Sign up to set email alerts
|

One-Dimensional Molybdenum Thiochlorides and Their Use in High Surface Area MoSxChalcogels

Abstract: The new compounds α‐ and β‐MoSCl3 and MoSeCl3 are prepared by chemical vapor transport reaction of MoCl3 and elemental S or Se (sealed silica tubes, 48 h, 400 → 200 °C for α‐MoSCl3 and MoSeCl3 and 400 → 140 °C for β‐MoSCl3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 45 publications
2
28
0
Order By: Relevance
“…The weak peak at 227.8 eV (Figure C) belongs to the S 2s energy . In addition, the two peaks at 165.2 (S 2p 1/2 ) and 163.7 eV (S 2p 3/2 ) deriving from S 2p energy represent the S 2− groups (Figure D),[18a,21,22] and the weak peak at 168.8 eV suggests the presence of a small quantity of SO 4 2− impurity originating from adventitious oxidation of S 2− . SEM images of MoS 4 ‐Ppy (Figure E) show a granular morphology with a granule size of ≈300 nm, similar to the reported Ppy morphology.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The weak peak at 227.8 eV (Figure C) belongs to the S 2s energy . In addition, the two peaks at 165.2 (S 2p 1/2 ) and 163.7 eV (S 2p 3/2 ) deriving from S 2p energy represent the S 2− groups (Figure D),[18a,21,22] and the weak peak at 168.8 eV suggests the presence of a small quantity of SO 4 2− impurity originating from adventitious oxidation of S 2− . SEM images of MoS 4 ‐Ppy (Figure E) show a granular morphology with a granule size of ≈300 nm, similar to the reported Ppy morphology.…”
Section: Resultsmentioning
confidence: 98%
“…The spectral peaks at 235.8 eV (Mo VI 3d 3/2 ) and 233.1(Mo VI 3d 5/2 ) eV (Figure C) indicate the Mo 6+ oxidation state as expected for the presence of the MoS 4 2− group. The weak peak at 227.8 eV (Figure C) belongs to the S 2s energy . In addition, the two peaks at 165.2 (S 2p 1/2 ) and 163.7 eV (S 2p 3/2 ) deriving from S 2p energy represent the S 2− groups (Figure D),[18a,21,22] and the weak peak at 168.8 eV suggests the presence of a small quantity of SO 4 2− impurity originating from adventitious oxidation of S 2− .…”
Section: Resultsmentioning
confidence: 98%
“…19 The crystal structures of two forms of MoSCl 3 obtained from crystals grown at high temperature found that both contain Mo(IV) as Mo 2 units and disulfide groups, and not Mo(V). 20 It is unclear if MoSCl 3 prepared at low temperatures from MoCl 5 and S(SiMe 3 ) 2 or Sb 2 S 3 contains Mo(V), 21,22 while MoSCl 4 is unknown. 19 In order to allow comparisons with the WOCl 4 , WOCl 3 , WSCl 4 and WSCl 3 chemistry, we have examined the chemistry of MoOCl 3 with neutral chalcogenoethers and report here complexes of mono-and bi-dentate thio-, seleno-and telluroethers.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, chalcogels are prepared by the metathesis technique, wherein coordinative reactions between the chalcogenide anions with metal cations enable the formation of a gel . Utilizing this technique, synthesis of several chalcogenide chemistries like NiMoS 4 , CoMoS 4 ; CoMo 3 S 13 ; ZnSnS 4 , ZnSn 2 S 6 , ZnSn 4 S 10 ; CoS 5 ; and (MoS 2 ) 2 (MoS 4 ) 3 has been reported. In addition, some other approaches based on oxidative coupling, hydrolysis, and acid–base reactions have also shown to yield chalcogels.…”
Section: Introductionmentioning
confidence: 99%
“…31 Generally, chalcogels are prepared by the metathesis technique, wherein coordinative reactions between the chalcogenide anions with metal cations enable the formation of a gel. 32 37 has been reported. In addition, some other approaches based on oxidative coupling, hydrolysis, and acid−base reactions have also shown to yield chalcogels.…”
Section: Introductionmentioning
confidence: 99%